Molecular Characterisation of Faecal Bacterial Assemblages Among Four Species of Syntopic Odonates - Morrill, Andre (Springer New York LLC, 2025)
Factors such as host species, phylogeny, diet, and both timing and location of sampling are thought to influence the composition of gut-associated bacteria in insects. In this study, we compared the faecal-associated bacterial taxa for three Coenagrion and one Enallagma damselfly species. We expected high overlap in representation of bacterial taxa due to the shared ecology and diet of these species. Using metabarcoding based on the 16S rRNA gene, we identified 1513 sequence variants, representing distinct bacterial ‘taxa’. Intriguingly, the damselfly species showed somewhat different magnitudes of richness of ZOTUs, ranging from 480 to 914 ZOTUs. In total, 921 (or 60.8% of the 1513) distinct ZOTUs were non-shared, each found only in one species, and then most often in only a single individual. There was a surfeit of these non-shared incidental ZOTUs in the Enallagma species accounting for it showing the highest bacterial richness and accounting for a sample-wide pattern of more single-species ZOTUs than expected, based on comparisons to the null model. Future studies should address the extent to which faecal bacteria represent non-incidental gut bacteria and whether abundant and shared taxa are true gut symbionts.